(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2018)
Automotive industry remains one of the most conservative sectors of the economy in terms of using market forces for mobility of labor force. The main areas of activity in the field of personnel management in the enterprises of motor transport is the definition of the requirements of qualified personnel and its qualified selection. Requirements of modern economy are oriented on effective realization of personnel potential. The efficient functioning of the automotive industry is directly dependent on the provision of high quality human resources. Consequently, personnel management is a complex process that is complete based on a comprehensive solution to personnel problems, the introduction of new directions in the management and improvement of existing forms and methods of work. Automotive workers are a priority source of increasing labor productivity in today’s environment, and then the efficiency of production. Each employee should feel its significance in the production process, which will further reveal the creative potential of the individual. After all, the axiom is an assertion that man cannot create dissatisfaction. The creative process will facilitate the introduction of innovative factors in production, which in turn all are additional reserves of growth of productive indicators. The process of involving employees in the management process should be not nominal but real. Labor productivity is an important category, which is influenced by various factors. In the context of life safety, decent working conditions must be provided, and a positive affect the health of workers. To achieve a multiplicative socio-economic effect on improving the state of health and further will be the turn of the increase in labor productivity and so on in a spiral. Human resources management is a complex process that should be complete based on a comprehensive solution to human resources problems, the introduction of new directions in the management and improvement of existing forms and methods of work. To date, the quality of personnel and its attitude to work is the main factor of the competitiveness of the industrial structure, its viability and prosperity. The personnel play a decisive role in prosperity. Personnel is critical also in the situation of instability, crisis phenomena. The determining social factors for employees are the material situation, the socio-psychological climate in the collective, socio-political activity, the prospects for growth, the level of satisfaction with work, social and household services, professionalization, socialization of the person, in formativeness and discipline.